THE MAP OF SMA/SMK ISLAMIC EDUCATION TEACHERS’ COMPETENCIES IN CENTRAL JAVA - Muzayanah, Umi; Muawanah, Siti; Noviani, Nur Laili; Zakiyah, Zakiyah; Oetomo, Setyo Boedi; Atmanto, Nugroho Eko (Balai Penelitian dan Pengembangan Agama Semarang, 2018)
Teachers of Islamic education in Indonesia have some problems. On the one hand, they are required to meet the standards of qualification, competencies, and certification. On the other hand, they have over-working hour due to the imbalance between the number of the teachers and the students. This fact will undoubtedly affect their work quality. The work quality of the teachers can be measured by five kinds of competences: pedagogic, personality, social, professional, and leadership. This research is aimed to measure the five competences of the teachers of Islamic Education in Senior High Schools and Senior Vocational Schools (both SMA and SMK) in Central Java, and it is also to examine the hypothesis that there is no significant difference in teachers’ competences in terms of their status: civil servants (PNS) or not (non-PNS), and certified or not. By using quantitative approach, the research has two important findings. The first, the competency of the Islamic teachers in Central Java is on the medium level which have a score at 2.95 on a scale of 4.00. The pedagogic competence occupies the highest level with 3.25, in contrast the social competence is on the lowest one with 2.9. The second, there is no significant difference in competences between the teachers who are civil servants and those who are not. On the contrary, there is a significant difference in competences between the teachers who are certified and who are not certified yet.